Persepsi Mahasiswa terhadap Evaluasi Proyek Berbantuan Generative Artificial Intelligence pada Mata Kuliah Pengembangan Praktikum IPA - Septi Kurniasih; Vica Dian Aprelia Resti; Adi Nestiadi; Suroso Mukti Leksono (UNIB Press, 2026)
The rapid advancement of Generative Artificial Intelligence (GenAI) has transformed assessment practices in higher education, particularly in project-based learning. However, empirical evidence regarding students' perceptions of AI-assisted project assessment in preservice science teacher education remains limited. This study aimed to investigate students' perceptions of AI-assisted project assessment implemented in the final examination of the Science Practicum Development course. A descriptive survey design with a quantitative approach was employed. The participants consisted of 90 undergraduate students enrolled in the Science Education Study Program, Faculty of Teacher Training and Education, Universitas Sultan Ageng Tirtayasa, Indonesia. Data were collected using a 10-item Likert-scale questionnaire and analyzed descriptively through means, percentages, and standard deviations. The findings revealed that students generally held positive perceptions toward AI-assisted project assessment, with all questionnaire items obtaining mean scores above 3.90. The highest-rated indicators were AI's ability to support idea generation (M = 4.32) and its role in encouraging critical thinking during project completion (M = 4.32). Students also perceived that AI improved project quality, promoted autonomous learning, and did not diminish their understanding of course content. Nevertheless, 5% of the respondents strongly disagreed that AI helped them complete the project effectively, while 13% did not believe that using AI enhanced their readiness for their future teaching profession. These findings suggest that although AI-assisted project assessment is well accepted by preservice science teachers, its effectiveness depends on students' AI literacy, critical thinking skills, and clear institutional guidelines for responsible AI use. Therefore, integrating AI into project-based assessment should be accompanied by the development of AI literacy, ethical awareness, and reflective practices to better prepare future science teachers for AI-integrated educational environments.